Profil LDL dan HDL Serum puyuh Jepang (Coturnix-coturnix japonica L.) setelah Pemberian Suplemen Serbuk Kunyit (Curcuma longa L.) - Sukarman Hadi Jaya Putra (Biota, 2018)
The purpose of this study was to determine the effect of supplementation of turmeric powder (Curcuma longa L.) before mature sex to the level of High Density Lipoprotein (HDL) and Low Density Lipoprotein (LDL) serum quail of Japan (Coturnix coturnic japonica L.). This study uses an experimental method with completely randomized design pattern. The test animal used is 45 female Japanese quail of female divided into 3 groups, namely; P0: Japanese quail that is not given turmeric powder, P1: Japanese quail given turmeric powder with dose 54 mg/quail/day, P2: Japanese quail given turmeric powder with dose 108 mg/quail/day. Each group consists of 5 repetitions. Levels of HDL and LDL serum were taken at the Japanese quail. The data obtained were analyzed uses analysis of variance (ANOVA) and continued with Duncan test with 95% confidence interval (α = 0.05). The result showed that the powder of turmeric before genital effect (P˂0.05) increased the HDL level and decreased the LDL level of Japanese quail. Provision of turmeric powder at dose of up to 108 mg/quail day were relatively higher raising serum HDL levels and relatively higher lowering LDL levels of Japanese quail.